Analisis Dampak Pariwisata Kampung Coklatdalam Aspek Ekonomi dan Sosial Masyarakat - Kadeni, Ninik Srijani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2019)
At present the existence of the tourism sector has become a concern of the community so that in various regions new tourist spots have emerged. Similarly, in Blitar, there are also many new tourist sites built, one of which is brown village tourism. With the construction of tourist attractions will have an impact on the economic and social community. This study aims to describe the impact of tourism on the economy and society. The research method used to answer these problems is to use a descriptive qualitative approach. Data obtained using observation and interviews, while data analysis three stages, namely data reduction, data display and verification. The results of the study show that the village tourism in chocolate has animpact on the economy and society.